2011
DOI: 10.4028/www.scientific.net/ddf.311.167
|View full text |Cite
|
Sign up to set email alerts
|

Implanted Impurities in Wide Band Gap Semiconductors

Abstract: Wide band gap semiconductors, mainly GaN, have experienced much attention due to their application in photonic devices and high-power or high-temperature electronic devices. Especially the synthesis of InxGa1-xN alloys has been studied extensively because of their use in LEDs and laser diodes. Here, In is added during the growth process and devices are already very successful on a commercial scale. Indium in nitride ternary and quaternary alloys plays a special role; however, the mechanisms leading to more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Simulations using a variety of lattice parameters attributed for bulk ZnO were done in order to compare with the experimental results obtained by M. E. Mercurio et al [22] (V zz = 1.58(2) ⇥ 10 21 V /m 2 corresponding to the frequency ! 0 = 29.9(1) M rad/s) and by H. Wolf et al parameters of the samples used in these works were not reported and quite an amount of different lattice parameters for bulk ZnO can be found [5,9,20]. Simulations were then performed with the parameters reported by H. Sowa and H. Ahsbahs [20], a = 3.2489Å and c = 5.2053Å, resulting in a V zz = 1.428 ⇥ 10 21 V /m 2 .…”
Section: Technical Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations using a variety of lattice parameters attributed for bulk ZnO were done in order to compare with the experimental results obtained by M. E. Mercurio et al [22] (V zz = 1.58(2) ⇥ 10 21 V /m 2 corresponding to the frequency ! 0 = 29.9(1) M rad/s) and by H. Wolf et al parameters of the samples used in these works were not reported and quite an amount of different lattice parameters for bulk ZnO can be found [5,9,20]. Simulations were then performed with the parameters reported by H. Sowa and H. Ahsbahs [20], a = 3.2489Å and c = 5.2053Å, resulting in a V zz = 1.428 ⇥ 10 21 V /m 2 .…”
Section: Technical Detailsmentioning
confidence: 99%
“…The solubility of CdO in ZnO, besides being low, depends strongly on the growth conditions and technique that is used. Concerning PAC studies, ZnO bulk crystals have been studied using different probes [9] but, for technological purposes, thin films must be used. Thus, in this study, thin films of ZnO and Cd x Zn 1 x O (x = 0.16) were investigated.…”
Section: Case Studiesmentioning
confidence: 99%
“…In this work we present temperature dependent PAC measurements of 111m Cd and 117 Cd implanted into AlN. The obtained results are compared to previous 111 In measurements, that showed a complex of 111 In and a nitrogen-vacancy that forms during the annealing of the samples and is stable up to high temperatures [4]. Furthermore, it can be shown, that this complex is not formed with Cd when measured at room temperature [5], which indicates that Cd traps no defects.…”
mentioning
confidence: 49%
“…4, although a second probe environment with a much larger EFG is observed [4]. Due to the fact, that the PAC-state is the same in both probes, this is an additional evidence, that Cd is incorporated on substitutional Al-sites which is known for In.…”
Section: M Cd In Aln and Comparison With 111 In In Alnmentioning
confidence: 89%
“…Recent PAC studies suggest that Indium in GaN and AlN tends to trap a nitrogen vacancy, which may strongly influence the properties of InGaN and AlInN alloys and may play a role in the above mentioned mechanisms of exciton localisation [4]. PAC measurements using the probes 117 Cd, 111m Cd and 181 Hf show that this probe-vacancy complex does not form at other heavy impurities and is a peculiarity of In in IIInitrides [5]. In these studies the radioactive probes were introduced by ion implantation.…”
mentioning
confidence: 99%